Fast and Easy Phage-Tagging and Live/Dead Analysis for the Rapid Monitoring of Bacteriophage Infection - Low, Hui Zhi; Böhnlein, Christina; Sprotte, Sabrina; Wagner, Natalia; Fiedler, Gregor; Kabisch, Jan; Franz, Charles M. A. P. (Frontiers in Microbiology, 2020)
Use of bacteriophages, which are viruses that kill bacteria, for biocontrol of pathogens and antimicrobial resistant bacteria has become increasingly important in recent years. As traditional culture-based methods are laborious and time-consuming, practicable use of bacteriophages will hinge on development of rapid and high throughput methods to analyze, characterize and screen large bacteriophage libraries. We thus established a novel method to fluorescently tag bacteriophages for virus screening and interaction studies, without the need for complicated and laborious purification procedures or genetic engineering of viruses to express fluorescent proteins. Bacteriophage PMBT14 was tagged using DNA dye Syto 13. Simply by using a membrane filter, tagged bacteriophages can be separated from non-sequestered excess dye rapidly, effortlessly and cheaply. The procedure takes less than 30 minutes and makes use of simple laboratory consumables that are already commonly used for bacteriophage preparations. As proof-of concept, we present here flow cytometric methods to analyze bacteriophage binding, infection and killing that are very accessible for high throughput analysis. We show that the resulting fluorescently tagged bacteriophage can be used to specifically stain its host bacterium Pseudomonas fluorescens DSM 50090. Individual fluorescent bacteriophages, their binding to and initial infection of bacteria could also be observed using confocal microscopy. The infection process was halted by the metabolic inhibitor sodium azide, suggesting a requirement of host metabolic processes for penetration by PMBT14. Flow cytometric live/dead assays was used a complementary method to determine bacteriophage infection of its host. We made preliminary efforts to adapt the tagging method to two other bacteriophages and discuss potential pitfalls and solutions in the use of tagged phages. Fluorescent phage tagging has previously been demonstrated to facilitate analysis of bacteriophage-host interactions. The method adopted in this study makes it fast, easy as well as cost effective.